THE PSYCHOLOGY OF WORSHIP IN THE MAURITIAN BHOJPURI FOLK SONGS - Dawosing, Jayganesh (PEOPLE: International Journal of Social Sciences, 2019)
Research Objectives: My paper aims at studying the psychology of worship in the Mauritian Bhojpuri folk songs. Songs from the Mauritian ‘Geet-Gawai’ (Bhojpuri songs sung before the wedding ceremony in Mauritius) will be analysed. Themes like pantheism, fear and awe in religion, nature worship or nature mysticism will be discussed. How do these singers perceive worship? Which theories are reflected in these songs? For how long will this tradition of worship exist?Methodology: Besides discourse analysis, interviews with the singers have shed light on these questions.Research Findings: Mauritian Bhojpuri folk songs depict the belief that reality is same as divinity. Everything is part of a merciful and eternal God. Theory of Pantheism of Baruch Spinoza prevails in the analysis where a similarity is also seen in the Vedas-philosophy of Advaita (Non-Dualism). This ceremony depicts that there are no barriers of caste and class as it contributes in the making of a strong multiracial community identity. It is no longer only for women as men are also actively participating in it.